Efficacy of Artesunate-mefloquine for Chloroquine-resistant Plasmodium vivax Malaria in Malaysia: An Open-label, Randomized, Controlled Trial - Grigg, Matthew J. (2016)
Background: Chloroquine (CQ)-resistant Plasmodium vivax is increasingly reported throughout southeast Asia. The efficacy of CQ and alternative artemisinin combination therapies (ACTs) for vivax malaria in Malaysia is unknown. Methods: A randomized, controlled trial of CQ vs artesunate-mefloquine (AS-MQ) for uncomplicated vivax malaria was conducted in 3 district hospitals in Sabah, Malaysia. Primaquine was administered on day 28. The primary outcome was the cumulative risk of treatment failure by day 28 by Kaplan–Meier analysis. Results: From 2012 to 2014, 103 adults and children were enrolled. Treatment failure by day 28 was 61.1% (95% confidence interval [CI], 46.8–75.6) after CQ and 0% (95% CI, 0–.08) following AS-MQ (P < .001), of which 8.2% (95% CI, 2.5–9.6) were early treatment failures. All patients with treatment failure had therapeutic plasma CQ concentrations at day 7. Compared with CQ, AS-MQ was associated with faster parasite clearance (normalized clearance slope, 0.311 vs 0.127; P < .001) and fever clearance (mean, 19.0 vs 37.7 hours; P = .001) and with lower risk of anemia at day 28 (odds ratio = 3.7; 95% CI, 1.5–9.3; P = .005). Gametocytes were present at day 28 in 23.8% (10/42) of patients following CQ vs none with AS-MQ (P < .001). AS-MQ resulted in lower bed occupancy: 4037 vs 6510 days/1000 patients (incidence rate ratio 0.62; 95% CI, .60–.65; P < .001). One patient developed severe anemia not regarded as related to their AS-MQ treatment. Conclusions: High-grade CQ-resistant P. vivax is prevalent in eastern Malaysia. AS-MQ is an efficacious ACT for all malaria species. Wider CQ-efficacy surveillance is needed in vivax-endemic regions with earlier replacement with ACT when treatment failure is detected.